Do Patients With Chronic Low Back Pain Benefit From Early Intervention Regarding Absence From Work?: A Randomized, Controlled, Single-Center Pilot Study. Issue 21 (1st November 2016) - Norbye, Anja Davis; Omdal, Aina Vedvik; Nygaard, Marit Eikrem; Romild, Ulla; Eldøen, Guttorm; Midgard, Rune
Abstract : Supplemental Digital Content is available in the text Abstract : Study Design: A randomized, controlled, single-center pilot study. Objective: The aim of this study was to investigate the feasibility of running a trial to explore if early intervention in individuals with chronic low back pain (CLBP) would lead to an early return to work (RTW) and reduce sick leave during 12 months of follow-up compared with patients on a 3-month waiting list. Summary of Background Data: Back pain is the reason for numerous absent days from work. In Norway, the government initiated a priority program, Earlier Return to Work (ERTW), to reduce work absences through early intervention. However, no proper evaluation has been performed on populations with CLBP. There is no consensus on how RTW should be measured. Only a few studies have examined how waiting time affects RTW. Methods: Fifty-eight patients were included in the study. The group with early intervention was examined within 2 weeks, and the group on the waiting list was examined after 12 weeks. The intervention was identical in both groups and consisted of an outpatient, intensive back school. The data were obtained by questionnaire after 3, 6, and 12 months. The primary outcome was absence from work. Results: The sample size in a full-scale study must comprise at least 382 patients on the basis of the assumptions in the pilot. In the pilot study, early intervention directly compared with an ordinary waiting list did not significantly affect the number of sick leave days after 12 months of follow-up. Conclusion: A prerequisite for launching a full-scale clinical trial is a redesign of the intervention, an improvement of procedures concerning inclusion and randomization, and finally a more precise definition of RTW. Level of Evidence: 3